Analisis Regresi Linear Untuk Memprediksi Kriteria Pengaruh Penjualan Mobil Honda Civic dan Toyota Camry pada Kota Surabaya - Alim Citra Aria Bima; Pratiwi Susanti; Fatim Nugrahanti (Bulletin of Information Technology (BIT), 2022)
Vehicle is one of the needs that is owned by some people. Online sales that sell vehicles either individually or through third party dealers. A website that has an advertising business for free or paid to help several sellers make transactions digitally, easier and buyers get what they want faster. Researchers used sample data from olx.com with a coverage area in the city of Surabaya which will be used in this study. The researcher wants to know whether the color variable or other variables on the object of research on Honda Civic and Camry vehicles can affect sales or not by using the Linear Regression method. In this study the authors used two samples of the dependent variable and each of them used five samples of the independent variables. Based on the results of the analysis that has been done, it turns out that the selling price of the Honda Civic which affects sales is the coefficient of the blue and black colors, while the white color does not affect the selling price for the Honda Civic brand. While the data on the selling price of the Toyota Camry are black and white which affect the selling price